Fibromialgia ¿Qué deben saber y evaluar los profesionales de Enfermería? (2011)
ABSTRACT: In the current text a theoretical fibromyalgia review is made. Disease of unknown etiology, characterized by localized pain, usually in muscles, tendon, joint and visceral zones. Physiopathology, evaluation, diagnosis and interventions of the disease are reviewed, aiming to strengthen the empiric pattern of knowledge, and improve the patient care under the nursing perspective.